Understanding the types of knowledge representations that meet non‐profit organizations' knowledge needs. Issue 1 (2014) - Rathi, Dinesh; Given, Lisa M.; Forcier, Eric
ABSTRACT: The not‐for‐profit sector is an important area for research, since the organizations operating in this domain contribute in many ways to our society (e.g., social value and GDP). Non‐profit organizations (NPOs) are highly knowledge‐oriented units. Knowledge management (KM) has been researched in breadth and depth in FPOs, where it has been demonstrated that KM plays a significant role in the success of these organizations. According to the literature, KM is equally important to non‐profits, and yet the sector has received comparatively scant attention in the KM literature. There is limited understanding on the knowledge needs of NPOs and thus, this paper seeks to provide insight into the NPO‐KM landscape. The authors conducted multi‐phase research with NPOs operating in different parts of Canada, including an online survey of Canadian charities. Through the analysis of survey results, twelve broad categories of knowledge types and their sub‐categories relevant to NPOs have been identified. This paper aims to contribute generally to the growing body of KM literature (i.e., beyond dichotomous model of tacit and explicit knowledge) and more specifically to the NPO‐KM space.